Behaviour of concrete beams reinforced using basalt and steel bars under fire exposure. (1st July 2021) - Hassan, Ahmed; Khairallah, Fouad; Elsayed, Hend; Salman, Amany; Mamdouh, Hala
Highlights: Higher tension stiffening of BFRP bars is addressed by gathering them with steel bars. Efficiency of steel bars with BFRP bars at normal temperature and under fire exposure is investigated. Degradation resistance of BFRP bars upon fire exposure (500 °C) is predicted. Finite element simulation results are verified. Accuracy of reduction coefficient in Branson's equation is investigated. Abstract: Basalt bars for concrete reinforcement, known as basalt fiber-reinforced polymers (BFRPs), are new natural inorganic materials with distinct mechanical properties that have been used recently in the construction field. Generally, the FRPs bars have no yield before the brittle failure as steel bars and their behavior, when exposed to fire, is still under investigation, this paper presents an experimental and theoretical study to get more knowledge about the characteristics and the fire resistance of a concrete beam reinforced using BFRPs and BFRPs mixed with steel bars. Eight half-scale concrete beams were constructed and tested up to failure at room temperature and under direct fire at 500 °C for 2 h. The basalt-to-steel percentage is the main parameter of this study. The BFRP-to-main-steel-bar replacement percentages are 100%, 67%, and 33% as three tension reinforcement bars were used. The results are discussed in terms of load capacity, cracking behaviour, and failure modes. Moreover, the experimental results are compared with theoretical calculations according to the ACI code and with numerical results obtained using the ANSYS finite element program. The results show that the beams with both steel and basalt reinforcement showed a better shear strength, enhanced crack stiffness, and lower degree of brittleness at failure. Our results also showed that the BFRPs beams yielded a better degradation resistance when the beams were exposed to fire as the failure load reduction factor for the BFRPs beam was 6.17% compared with that of steel beam which was 22.32%. More studies are needed to justify our observations in details and determine their applicabilities under different conditions.